Values and physical activity among sports science students in France and China: a transcultural analysis - Liang, Yan; Rascle, Olivier; Hanel, Paul H. P.; Yang, Jian; Souchon, Nicolas (Frontiers in Psychology, 2024)
Objective The aim of this study was to analyze the relationships between values and physical activity in France (a Western European individualistic country) and in China (an East Asian collectivist country). Method Six hundred and twenty-seven sport science students in France (N = 308, Mage = 18.99, SD = 1.64) and China (N = 319, Mage = 20.44, SD = 1.09) completed the International Physical Activity Questionnaire long version and the Portrait Values Questionnaire. Results In both France and China, moderated regression analysis revealed that hedonism positively/negatively predicted physical activity, while security-societal, security-personal, and conformity-rules values negatively predicted physical activity. In contrast, stimulation and universalism-nature values positively predicted physical activity only in France. In China, benevolence and benevolence-care positively predicted physical activity, while power dominance negatively predicted physical activity. Additionally, we found evidence of measurement invariance of the value questionnaire. Discussion and conclusion Our findings add to the literature by showing that the value–behavior link is partly the same across countries and partly different. Further, our findings show that for certain populations, the previously established hierarchy of human values does not replicate.